Interaction of Nanomaterials with Plants: What Do We Need for Real Applications in Agriculture? - Pérez-de-Luque, Alejandro (Frontiers in Environmental Science, 2017)
The number of published researching works related with applications of nanomaterials in agriculture is increasing every year. Most of such works focus on the synthesis of nanodevices, their characteristics as nanocarriers for controlled release of active substances, and their interaction (either positive or negative) with plants or microorganisms under controlled conditions. Important knowledge has been gained about the uptake and distribution of nanomaterials in plants, although there are still gaps regarding internalization inside plant cells. Nanoparticle traits and plant species greatly affect the interaction, and nanodevices can enter and move through different pathways (apoplast vs. symplast), what influences their effectiveness and their final fate. Depending on the effect we are expecting for a nanocarrier, the application method might be critical. However, in order to get that research used in the field, some problems must be addressed. First, the cost for escalating the production of nanodevices must be affordable with the current production cost of agricultural goods. Second, we need to be sure that a technology is safe before spreading it into the environment. Third, consumers will distrust a technology unfamiliar for them in the same way that happened with transgenic crops. We need to broaden our horizons and start looking for real practical approaches, filling the main gaps that hamper our jump from laboratory research into field applications.